Exploring the Impact of Parent-Adolescent Conflict on Adolescent Academic Performance, Retention, and Concentration in the South Dayi District, Ghana - Amedi, Wisdom; Pufaa, Felicia Esinam (European Scientific Journal, ESJ, 2026)
Parent-adolescent conflict is a global problem that confronts most families. It remains a key concern due to its consequences on emotional, social, and psychological well-being, as well as its long-term implications for the family and adolescents’ overall development. This study explored the impact of parent-adolescent conflict on adolescents’ academic performance, retention, and concentration in South Dayi District, Ghana. The objectives of the study were to examine the causes of adolescent-parent conflict on adolescents’ academic performance, retention, and concentration, and the consequences of parent-adolescent conflict on adolescents’ academic performance, retention, and concentration. This study adopted a qualitative approach and a case study design. Thirty-two (32) participants were purposively selected from two Senior High Schools in the South Dayi District, and the data were thematically analyzed. The findings showed that poverty, neglect of parental obligations, broken homes, early relationships with the opposite sex, and single parenting, among others, were the leading causes of conflict between parents and adolescents. The study also revealed that parent-adolescent conflict resulted in school dropouts, lack of concentration in school, and early relationships with the opposite sex, among others. It was concluded that the adolescent stage is delicate; therefore, effective interventions and strategies must be initiated by the government in collaboration with district authorities and Non-Governmental Organizations (NGOs), to enable educators, parents, and school counsellors to help adolescents who may be experiencing academic difficulties as a result of conflict at home. It is recommended that schools develop comprehensive counselling services, including frequent counselling sessions, to help students facing challenges at home due to clashes with parents to enable them to focus on their academic work and manage their time properly. In addition, the Government of Ghana, in collaboration with the Ministry of Gender, Children, and Social Protection, should support poor and single parents with alternative Income-Generating Activities (IGAs) to enable them to effectively provide the needs of their adolescents.